Association of serum copper (Cu) with cardiovascular mortality and all-cause mortality in a general population: a prospective cohort study - Xiaozhong Li; Jitao Ling; Qingwen Hu; Changchang Fang; Kaibo Mei; Yifan Wu; Jingyi Huang; Qin Ling; Yixuan Chen; Peng Yu; Xiao Liu; Juxiang Li (BMC, 2023)
Abstract Background Copper (Cu) homeostasis and Cu-induced cell death are gaining recognition as crucial processes in the pathogenesis of cardiovascular disease (CVD). Circulating Cu associated with CVD and mortality is yet to be fully elucidated. Objective This national prospective cohort study is to estimate relationship between serum Cu and the risk of CVD and all-cause mortality. Methods This study included participants from the National Health and Nutrition Examination Survey 2011-2016. Weighted Cox proportional hazards regression analysis and exposure-response curves were applied. Results This included 5,412 adults, representing 76,479,702 individuals. During a mean of 5.85 years of follow-up (31,653 person-years), 96 CVD and 356 all-cause mortality events occurred. Age and sex-adjusted survival curves showed that individuals with higher levels of serum Cu experienced increased CVD and all-cause death rates (tertiles, p < 0.05). Compared with the participant in tertile 1 of serum Cu (< 16.31 mol/L), those in tertile 3 (≥ 19.84 mol/L) were significantly associated with CVD mortality (HR: 7.06, 95%CI: 1.85,26.96), and all-cause mortality (HR: 2.84, 95% CI: 1.66,4.87). The dose-response curve indicated a linear relationship between serum Cu and CVD mortality (p -nonlinear = 0.48) and all-cause (p -nonlinear = 0.62). A meta-analysis included additional three prospective cohorts with 13,189 patients confirmed the association between higher serum Cu and CVD (HR: 2.08, 95% CI: 1.63,2.65) and all-cause mortality (HR: 1.89, 95%CI: 1.58,2.25). Conclusion The present study suggests excessive serum Cu concentrations are associated with the risk of CVD and all-cause mortality in American adults. Our findings and the causal relationships require further investigation. Graphical Abstract